Correlation between level of albumin and glycosylated haemoglobin in south indian patients with type 2 diabetes mellitus - S. SAKTHI DASAN; C. SUTHAKARAN (International Journal of Pharma and Bio Sciences, 2017)
Type 2 diabetes mellitus in Asian Indian people is characterized by a young age of onset and occurrence at low levels of BMI. Available data also suggest that the susceptibility of Asian Indian people to the complications of diabetes mellitus differs from that of white populations. To investigate whether a correlation exists between HbA1c and serum albumin levels in South Indian patients with type 2 diabetes mellitus, a prospective study of electronic case records of type 2 diabetes patients presenting to the institution as part of the routine care was undertaken, between June 2015 and July 2016. Those who attended the diabetes clinic for screening but were not found to be diabetic (HbA1c <6.5%) served as the reference group. Fasting and post-prandial blood glucose, HbA1clevels and serum albumin levels were measured. Spearman correlation and multiple linear regression analysis was done to test the dependence of albumin on HbA1c, fasting blood sugar as well as post-prandial blood sugar levels. The values of HbA1c values were higher when the levels of albumin were low and lower when the level of albumin level was high. Serum albumin level was significantly lower in the reference group of patients when compared with control group and correlated negatively with HbA1C levels. Although a negative correlation was found between the levels of HbA1c and albumin in control and reference groups, the relationship between the variables was weak. Since HbA1c has become the standard tool for monitoring glycaemic control in patients with diabetes, the values should be interpreted with caution in our population.